Surdez e preconceito : uma análise a partir dos estudantes surdos e dos pais de surdos - Araújo, Andressa Araújo de (2018)
Referring to deafness is, automatically, allude the prejudice. After all, the deaf, for a long period of history, they were not accepted in society; on the contrary, they were distanced and had not meet their social and educational needs. The present study deal with deafness and prejudice and aims to understand the experience of prejudice suffered by deaf students during the school period, in the inclusive proposal, and to analyze the conception of the deaf parents about the prejudice suffered by their deaf children. For this purpose, four studies related to deafness and prejudice were carried out. In Study 1, a conceptual analysis was presented concerning the theme. In the Study 2, was conducted a systematic review, involving the articles that correlate the theme deafness and prejudice, in the period between January 2006 and December 2016, in two databases: SciELO and Pepsic. The objective was to identify what has been investigated and what still needs to be researched for the subject in question and, from there, to develop a study schedule for future research. Bibliometric and content analyzes were carried out on 15 articles that fulfilled the inclusion criteria of the research. The results evidenced the need of further studies in the area. Study 3 aimed to understand the experience of prejudice experienced by the deaf university students during their school career in the inclusive proposal. For this purpose, a focal group with five deaf college students was performed out and, to verify the data, was used the content analysis proposed by Bardin. The results of this study presented, through the deaf discourses about the school experience until High School, manifestations of prejudice such as: the obligation to oralize in the classroom; the absence of interpreters; bullying; verbal violence; discrimination and exclusion. From the same subjects of study and analyzes, an article (Study 4) on School Inclusion of the Deaf was produced, aiming to understand the experience of deaf university students, during their trajectory, in the inclusive proposal. The results shows that the inclusion policies do not happen effectively for all: what happens is integration or a (pseudo) inclusion. It was perceived that the experiences of schooling of the deaf in this study were determined by precarious teaching conditions, compromised by the difficulties of their access to the natural language, by the lack of interpreter and by the predominance of the Portuguese language in the teaching. Later, was made an pioneering study (Study 5) that objective the analyze of understanding of deaf parents about the prejudice suffered by their children. Eight parents of deaf people participated, who gave an interview based on thematic axes that were analyzed through IRAMUTEQ software. The results of this study showed, through the parents' talks, how frequent the acts of prejudices suffered by the deaf, especially by health professionals, the family and the school. According to the five studies, the conclude is, in spite of advances in the laws, aiming, above all, at egalitarian treatments and without prejudice, it is also observed how common is the clinical medical view of society regarding deafness and, as a consequence, acts of prejudice.